A green process for recovery of 1-propanol/2-propanol from their aqueous solutions: Experimental and MD simulation studies. (February 2017) - Gupta, Bhupender S.; Taha, Mohamed; Lee, Ming-Jer
Graphical abstract: Highlights: A green conceptual design for separating propanols from their aqueous solutions is proposed. TRIS is biocompatible and non-volatile and can be used as an auxiliary agent for the separation. Isobaric VLE data for 1-propanol/2-propanol + water + TRIS were measured at 101.3 kPa. The azeotropic compositions are significantly shifted in the presence of TRIS. Intermolecular interactions were studied with fluorescence, COSMO-RS, and MD simulation. Abstract: In the present study, we have found that a common and relatively inexpensive biological buffer tris(hydroxymethyl)aminomethane (TRIS) is potentially applicable to shift the azeotrope compositions of aqueous solutions of 1-propanol and 2-propanol. By taking the advantage of our findings, we are proposing a green process for the recovery of these organics from their respective aqueous solutions. In order to confirm the effect of TRIS buffer on vapor–liquid equilibrium behavior of the aqueous propanol systems, we measured the isobaric vapor–liquid equilibrium (VLE) data at 101.3 kPa for the 1-proponol + water + TRIS and 2-propanol + water + TRIS systems over the azeotropic range with various concentrations of TRIS (0.02, 0.04, 0.08, and 0.12 in mole fraction). The binary interaction parameters were obtained for TRIS with water, TRIS with 1-propanol, and TRIS with 2-propanol by correlating the new VLE data with the NRTL model. The isobaric VLE properties for the investigated propanol + water mixtures in the presence of various concentrations of TRIS were also predicted with the conductor-like screening model COSMO-RS. Based on the predicted excess molar enthalpies ( H E m ) from the COSMO-RS, the interactions between all constituent pairs of molecules were estimated. To explore the mechanism of TRIS-based separation of 1-propanol/2-propanol from their aqueous solutions, the interactions between different pairs of molecules were also investigated by using fluorescence analysis and Molecular Dynamic (MD) simulation. In comparison with the conventional corrosive inorganic salts and volatile organic entrainers, TRIS is non-corrosive, non-volatile, and almost totally recyclable. With the aid of TRIS, a cleaner separation process is proposed in the present study for recovery of 1-propanol and 2-propanol from their aqueous solutions based on buffer-swing distillation.